2020
DOI: 10.3390/cells9041055
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Epithelial–Mesenchymal Transition and Tumor Microenvironment in Helicobacter pylori-Induced Gastric Cancer

Abstract: Helicobacter pylori (H. pylori) is one of the most common human pathogens, affecting half of the world's population. Approximately 20% of the infected patients develop gastric ulcers or neoplastic changes in the gastric stroma. An infection also leads to the progression of epithelial-mesenchymal transition within gastric tissue, increasing the probability of gastric cancer development. This paper aims to review the role of H. pylori and its virulence factors in epithelial-mesenchymal transition associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 309 publications
(267 reference statements)
4
82
0
1
Order By: Relevance
“…The occurrence of GC is the result of a combination of multiple factors. For example, long-term chronic stimulation of various inflammatory factors is a key factor leading to the occurrence of GC [23,24]. Previous studies have shown that sustained inflammation can cause downregulation of BDH2 expression [25].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of GC is the result of a combination of multiple factors. For example, long-term chronic stimulation of various inflammatory factors is a key factor leading to the occurrence of GC [23,24]. Previous studies have shown that sustained inflammation can cause downregulation of BDH2 expression [25].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric carcinogenesis is a complex, multifactorial process that is primarily stimulated by chronic inflammation (induced by H. pylori infection in the majority of cases); however, other processes such as the epithelial-mesenchymal transition (EMT) or intensified angiogenesis play a crucial role in GC progression [19][20][21][22][23]. Angiogenesis is a physiological process of the formation of the new blood vessels from the already existing ones.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infection is well known to cause chronic gastric in ammation and eventually GC. EMT and the tumor microenvironment contribute to H. pylori induced GC [44]. In this study, we demonstrated that IGFBP7 was highly expressed in GC samples with H. pylori infection.…”
Section: Discussionmentioning
confidence: 55%